Role of MRI pelvis in assessment of anorectal malformations : 2D versus 3D sequenes - Manal Hamdan Zaraa; Hasan Ali Elkiki; Mohamed Magdi Elbarbari; Rania Farouk Elsayed (Cairo : Manal Hamdan Zaraa, 2012)
Magnetic resonance imaging proven to be considerable value in evaluating patients with anorectal malformations . Comparing triplanar 2D MR images with reformatted images from a single 3D sequence has revealed no signifcant differences with regared to image quality and diagnostic information obtained . However , the mean acquisition time for the 3D sequence was notaby shorter than acquisition time for the 3D sequences in three planes
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: 2D MRI sequence; 3D MRI sequenece; ARM